The role of tumour biological factors in technical anatomical resectability assessment of colorectal liver metastases following induction systemic treatment: An analysis of the Dutch CAIRO5 trial. (April 2023) - Bolhuis, Karen; Bond, Marinde J.G.; Van Amerongen, Martin J.; Komurcu, Aysun; Chapelle, Thiery; Dejong, Cornelis H.C.; Engelbrecht, Marc R.W.; Gerhards, Michael F.; Grünhagen, Dirk J.; van Gulik, Thomas M.; Hermans, John J.; De Jong, Koert P.; et al.
Abstract: Background: Large inter-surgeon variability exists in technical anatomical resectability assessment of colorectal cancer liver-only metastases (CRLM) following induction systemic therapy. We evaluated the role of tumour biological factors in predicting resectability and (early) recurrence after surgery for initially unresectable CRLM. Methods: 482 patients with initially unresectable CRLM from the phase 3 CAIRO5 trial were selected, with two-monthly resectability assessments by a liver expert panel. If no consensus existed among panel surgeons (i.e. same vote for (un)resectability of CRLM), conclusion was based on majority. The association of tumour biological (sidedness, synchronous CRLM, carcinoembryonic antigen and RAS / BRAF V600E mutation status) and technical anatomical factors with consensus among panel surgeons, secondary resectability and early recurrence (<6 months) without curative-intent repeat local treatment was analysed by uni- and pre-specified multivariable logistic regression. Results: After systemic treatment, 240 (50%) patients received complete local treatment of CRLM of which 75 (31%) patients experienced early recurrence without repeat local treatment. Higher number of CRLM (odds ratio 1.09 [95% confidence interval 1.03–1.15]) and age (odds ratio 1.03 [95% confidence interval 1.00–1.07]) were independently associated with early recurrence without repeat local treatment. In 138 (52%) patients, no consensus among panel surgeons was present prior to local treatment. Postoperative outcomes in patients with and without consensus were comparable. Conclusions: Almost a third of patients selected by an expert panel for secondary CRLM surgery following induction systemic treatment experience an early recurrence only amenable to palliative treatment. Number of CRLM and age, but no tumour biological factors are predictive, suggesting that until there are better biomarkers; resectability assessment remains primarily a technical anatomical decision. Highlights: Role of tumour biological factors in resectability assessment of colorectal cancer liver-only metastases was evaluated. 31% of locally treated patients had early recurrence without repeat local treatment. Number of colorectal cancer liver-only metastases and age are predictive for early recurrence without repeat local treatment. Resectability assessment remains primarily a technical anatomical decision.